Burnout Without Borders: Exploring Burnout and the Validity of the Maslach Burnout Inventory Among Medical Students Across Four Countries in Africa - Oluwadiya, K S; Adeoti, A O; Usman, M I; Maison, P O M; Rahman, G A; Olasinde, A A; Mensah, S (West African journal of medicine, 2025)
There has been little or no cross-cultural validation study of the Maslach Burnout Inventory (MBI) from sub-Saharan Africa (SSA). This study aims to test three hypotheses among medical students in four selected countries - Ghana, Nigeria, Sierra Leone and Uganda in sub-Saharan Africa (SSA). This research utilized a cross-sectional design and employed an online self-administered questionnaire. The measurement of burnout was conducted utilizing the Maslach Burnout Inventory General Survey for Students (MBI-GS (S) on Google Form. The survey was distributed via WhatsApp to medical students enrolled in six medical schools across four countries. The statistical analysis was conducted using SPSS AMOS version 24 for Confirmatory Factor Analysis (CFA) with Structural Equation Modelling (SEM). The prevalence of burnout varied among the medical students in the four countries with Ghana (72.1%) and Nigeria (61.2%) higher than Sierra Leone (59.2%) and Uganda (47.7%). Confirmatory factor analysis showed that the 3-factor structure of the MBI-GS(S) fits both the overall sample and the samples from each of the four individual countries albeit after correlating error terms in the analysis. However, hypothesis 2, which posited structural invariance across the samples from the four countries, was only partially met as the model demonstrated configural invariance across the samples but not metric invariance. The results of our study provide empirical evidence supporting the presence of burnout among medical students, revealing significant disparities across the participating countries. While the MBI-GS (S) proved to be a useful tool for this assessment, our findings also highlight the challenges of achieving measurement invariance in cross-cultural research, underscoring the need for culturally adaptable methodologies.